Problem of optimum strategy modeling of multistage technological process control - Lysohor, V. M.; Sorokun, S. V. (Visnyk of Vinnytsia Politechnical Institute, 2010)
The problem of optimum strategy multistage technological process control, which determines the model of the state, model of supervision at presence of surges which influence both the object and the observed output value within the limits of stages and interstage connections is considered .